The crustal structure of Deception island (West Antarctica) by geophysical data - Levashov, S.; Korchagin, I.; Kozlenko, Yu.; Solovyov, V. (Український антарктичний журнал, 2006)
New results of the geophysical studies of deep inhomogeneities of crustal structures distribution that were obtained in the SW part of Bransfield Strait near the present Deception Island volcano are discussed. The geophysical data interpretation suggests a local character of the present submarine volcanic activity in the SE part of Deception Island. The magma source is associated with a rather local tectonic disturbance at a depth above 6km. The formation and evolution of this disturbance may caused by features of the distribution of marginal tensions during the interaction of the tectonic continuation of the Hero Fracture Zone and the tectonic disturbances of Bransfield Strait Fracture Zone in the area of Deception Island. По данным электромагнитных зондирований, полученным во время сезонных работ 9-й Украинской антарктической экспедиции, во внутренней бухте о. Десепшн выявлена область прогрева, расположенная недалеко от цепочки подводных вулканов в юго-восточной части острова. На глубинах 1,4–2,8км предполагается наличие интрузивного тела, которое создает источник прогревания в верхней части разреза. Подобные тела выявлены и в более глубоких горизонтах. Дані електромагнітних зондувань, отримані під час сезонних робіт 9-ї Української антарктичної експедиції у внутрішній бухті о. Десепшн, виявили наявність значної області прогріву в кальдері неподалік від підводних вулканів у південно-східній частині острова. На глибинах 1,4–2,8 км можлива наявність інтрузивного тіла, яке створює джерело прогріву у верхній частині розрізу. Подібні тіла виявлені також у більш глибоких горизонтах. Джерело магми пов’язане із локальним тектонічним порушенням на глибині більше 6 км. Формування і розвиток цього порушення можуть бути обумовлені особливостями розподілу граничних напруг під час взаємодії тектонічного продовження зони розломів Хіро і тектонічних порушень рифтової зони протоки Брансфілд.